Two Split-Time Artificial Insemination Programs in Suckled Beef Cows - J. Stevenson; S. L. Hill; D. M. Grieger; K C Olson; J. R. Jaeger; K. R. Harmoney; J. Ahola; G. E. Seidel; R. K. Kasimanickam (Kansas Agricultural Experiment Station Research Reports, 2018)
Successful programs to manipulate estrus and ovulation to maximize pregnancy outcomes in suckled beef cattle have been developed to limit animal handling and to eliminate the need to detect estrus, thereby providing more opportunity to incorporate AI to start the breeding season. The most successful and consistent synchronization scheme employs an intravaginal progesterone insert (controlled internal drug release, CIDR) in place for 7 d concurrent with GnRH treatment, and, upon removal of the insert, injection of PGF2α, followed by timed AI at 60 to 66 h concurrent with a second dose of GnRH (CO-synch + CIDR). Inseminating cows after expressed estrus increases pregnancy rate compared with cows that do not display estrus in a timed AI program. Identification of estrus can be accomplished easily by using estrus-detection patches, thus facilitating timing of AI to meet herd-specific situations. Varying AI timing has increased pregnancy rate in some, but not all studies. Rather than using 1 planned fixed-time AI for all cows, we tested split-time AI intervals, and used detection of estrus to optimally time AI relative to detected estrus. In previous research, in 2 separate experiments, estrus was detected by using estrus-detection patches at either 60 or 65 h after PGF2αand AI was conducted for cows in estrus. Remaining cows received a fixed-time AI at either 75 or 84 h, respectively. Administering GnRH to cows already detected in estrus at 60 or 75 h did not improve pregnancy rate. Additionally, administering GnRH at 60 or 75 h to cows not yet in estrus only improved pregnancy rate in cows that did not come into estrus during the interim before timed AI occurred at 75 or 84 h, respectively. Our objective was to determine which time combination for split-time AI would maximize pregnancy rate in suckled beef cows: 55 h (AI cows in estrus) + 75 h (receive GnRH at 55 h and AI at 75 h) or 65 h (AI cows in estrus) + 85 h (receive GnRH at 65 h and AI at 85 h).
Keywords: beef cattle; CIDR; estrus; split-time artificial insemination